Community engagement and knowledge translation: Progress and challenge in autism research. (October 2014) - Elsabbagh, Mayada; Yusuf, Afiqah; Prasanna, Shreya; Shikako-Thomas, Keiko; Ruff, Crystal A; Fehlings, Michael G
The last decade has seen significant growth in scientific understanding and public awareness of autism. There is still a long road ahead before this awareness can be matched with parallel improvements in evidence-based practice. The process of translating evidence into community care has been hampered by the seeming disconnect between the mainstream scientific research agenda and the immediate priorities of many communities. The need for community engagement in the process of translating knowledge into impact has been recognized. However, there remains little consensus or empirical data regarding the process of such engagement and how to measure its impact. We shed light on a number of engagement models and tools, previously advocated in health research, as they apply to autism research. Furthermore, we illustrate the utility of such tools in supporting identification of knowledge gaps and priorities, using two community-based case studies. The case studies illustrate that information generated from research is indeed relevant and critical for knowledge users in the community. Simple and systematic methods can support the translation and uptake of knowledge in diverse communities, therefore enhancing engagement with research and bridging research findings with immediate community needs.